Subjective experience : its fate in psychology, psychoanalysis and philosophy of mind - Eagle, Morris N. (Abingdon, Oxon ; New York, NY : Routledge, 2024)
"Morris N. Eagle explores the understanding and role of subjective experience in the disciplines of psychology, psychoanalysis, and philosophy of mind. Elaborating how different understandings of subjective experience give rise to very different theories of the nature of the mind, Eagle then explains how these shape clinical practices. In particular, Eagle addresses the strong tendency in the disciplines concerned with the nature of the mind to overlook the centrality of subjective experience in one's life, to view it with suspicion, and to reduce it to neural processes. Describing examples of research in which subjective experience is a central variable, Eagle provides an outline of a model in which the dichotomy of conscious and unconscious is supplemented by subjective experience as a continuum. This book is essential reading for psychoanalysts, psychoanalytic psychotherapists, psychologists and anyone wishing to gain a deeper understanding of the importance of theories of the mind to therapeutic practice"--
Consciousness and subjective experience in psychology -- Consciousness and subjective experience in psychoanalysis -- Consciousness and subjective experience in philosophy of mind -- Are consciousness and subjective experience uninvestigatable? -- Intersubjective experience -- Feelings and affects -- Consciousness and subjective experience as a continuum -- Some summing up and concluding comments.
Keywords: Subjectivity; Consciousness; Psychology; Psychoanalysis; PHILOSOPHY / Mind & Body; PSYCHOLOGY / Movements / Psychoanalysis